Bridging the ivory tower and industry: How university science parks promote university-industry collaboration? - Kang, Yankun; Liu, Ruiming; Yang, Bingyan (Research Policy, 2025)
We investigate the impact of university science parks (USPs)—platforms designed to foster university-industry (UI) connections, specifically focusing on their role in UI patent collaboration. Utilizing the introduction of USPs in China between 2006 and 2016, we find that they are associated with a notable 50.8 % increase in UI collaborative patents, equivalent to approximately 1.8 additional patents per year. We further proposed that USPs can facilitate UI collaboration through three mechanisms—spatial proximity, intermediary services, and knowledge complementarity—and provided corresponding empirical evidence to support these claims. Furthermore, measured by the patent citations, we also find that these parks significantly enhance the quality of UI collaborations. These results underscore the pivotal role of USPs as facilitators of interaction between academic institutions and industries.